Pengaruh Fungsi Pengawasan Dewan Perwakilan Rakyat Daerah (DPRD) Terhadap Penggunaan Anggaran Pendapatan Dan Belanja Daerah (APBD) Di Kabupaten Minahasa Selatan - Goni, Renaldy; Rorong, Arie; Tampi, Gustaf Budi (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract: In carrying out oversight functions, the Regional Representatives Council (DPRD) equippedwith special rights that can support the effectiveness of the work as one of the institutions of control in thearea. and most importantly that in determining whether or not accepted the draft budget proposed by theexecutive, the Regional Representatives Council (DPRD) had a very big right. Based on an evaluation ofthe State Audit Board (BPK) of the Republic of Indonesia through the representatives of North Sulawesi,assess the use of the Regional Budget (APBD) South Minahasa, from Fiscal Year 2009 to 2012 Budgetgets a "disclaimer, meaning that can not be assessed and checks in Budget 2014, to use the RegionalBudget (APBD) in 2013 there was an increase in ratings of disclaimer to the unnatural. This is due toRevenue and Expenditure Budget (APBD) South Minahasa District by each regional work units (SKPD)does not fit the designation and use of Revenue and Expenditure Budget (APBD) and assets much abusedby the head of the regional work units (SKPD) and subordinates. This study aims: "To analyze the effectof supervisory functions Regional Representatives Council (DPRD) to use the Regional Budget (APBD)South Minahasa District". The method of analysis in this research is quantitative descriptive analysismethod. Results of this research is that the supervision of Parliament is one of the determinant factorsincrease the effectiveness of the use of the budget, particularly in the South Minahasa District. In linewith the Strategic Plan (Restra) South Minahasa District Government which sets one of the priorityprogram is the use of the regional budget (APBD) is done effectively, efficiently and economically orientedpublic interest. Thus, efforts to increase the effectiveness of the use of local budgets is through an increasein the budget managers profesionalism apparatus itself by trying to implement i-budgeting.Keywords: Effect, Function Control, Parliament, Budget